2021
DOI: 10.1097/aln.0000000000003694
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Intraoperative Oxygen and Long-term Mortality: Subanalysis of a Multiple Crossover Cluster Trial

Abstract: Background Whether supplemental oxygen worsens long-term mortality remains unclear, with contradictory trial results. The authors therefore tested the hypothesis that supplemental oxygen (80% vs. 30%) increases the hazard for long-term mortality. Methods The authors conducted a post hoc analysis of a large multiple crossover cluster trial in which more than 5,000 colorectal surgeries on 4,088 adults were allocated to receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 26 publications
3
15
1
Order By: Relevance
“…In line, after a median followup of 2.3 years, a subsequent analysis of the same trial found increased long-term mortality in patients receiving 80% oxygen during cancer surgery (11). Contrarily, authors of other post-hoc analysis, combining mortality data from different RCTs, found that there was neither a difference in long-term mortality nor did they find differences in overall survival for patients randomly assigned to 30% vs. 80% FiO 2 (32,33). The median follow-up was 12.8 (3.8, 13.6) years in the trial by Greif,4.3 (3.6,4.8) years in the trial by Kurz, and 3.2 (0.5, 4.9) years in the study by Jiang (1,33,34).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In line, after a median followup of 2.3 years, a subsequent analysis of the same trial found increased long-term mortality in patients receiving 80% oxygen during cancer surgery (11). Contrarily, authors of other post-hoc analysis, combining mortality data from different RCTs, found that there was neither a difference in long-term mortality nor did they find differences in overall survival for patients randomly assigned to 30% vs. 80% FiO 2 (32,33). The median follow-up was 12.8 (3.8, 13.6) years in the trial by Greif,4.3 (3.6,4.8) years in the trial by Kurz, and 3.2 (0.5, 4.9) years in the study by Jiang (1,33,34).…”
Section: Discussionmentioning
confidence: 98%
“…Contrarily, authors of other post-hoc analysis, combining mortality data from different RCTs, found that there was neither a difference in long-term mortality nor did they find differences in overall survival for patients randomly assigned to 30% vs. 80% FiO 2 (32,33). The median follow-up was 12.8 (3.8, 13.6) years in the trial by Greif,4.3 (3.6,4.8) years in the trial by Kurz, and 3.2 (0.5, 4.9) years in the study by Jiang (1,33,34). This is in line with our finding that overall survival did not differ between high and low FiO 2 groups with a median follow-up of 3.28 (1.68, 4.97) years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors tested the effects of 80% versus 30% oxygen concentration on a composite of 30-day deep and organ-space SSIs, healing-related wound complications and mortality, and found that supplemental oxygen does not prevent major infections and healing-related complications after major intestinal surgery [ 30 ]. A recent post-hoc analysis of this study, including 3400 operations performed on 2800 patients, investigated patient long-term mortality [ 55 ]. After a median of 3 years, the incidence of death was no different in the 80% versus the 30% oxygen group (13% vs. 14%, 95% CI = 0.78–1.13; p = 0.493).…”
Section: Hyperoxia Effects On Surgical Cancer Patients—clinical and Experimental Datamentioning
confidence: 99%
“…After a median of 3 years, the incidence of death was no different in the 80% versus the 30% oxygen group (13% vs. 14%, 95% CI = 0.78–1.13; p = 0.493). The analysis of 995 colorectal cancer patients also showed that 80% inspired oxygen did not influence long-term mortality [ 55 ].…”
Section: Hyperoxia Effects On Surgical Cancer Patients—clinical and Experimental Datamentioning
confidence: 99%